2011
DOI: 10.1073/pnas.1101262108
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of the endoplasmic reticulum aminopeptidase-1 (ERAP1) reveal the molecular basis for N-terminal peptide trimming

Abstract: Endoplasmatic reticulum aminopeptidase 1 (ERAP1) is a multifunctional enzyme involved in trimming of peptides to an optimal length for presentation by major histocompatibility complex (MHC) class I molecules. Polymorphisms in ERAP1 have been associated with chronic inflammatory diseases, including ankylosing spondylitis (AS) and psoriasis, and subsequent in vitro enzyme studies suggest distinct catalytic properties of ERAP1 variants. To understand structure-activity relationships of this enzyme we determined c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
286
2
13

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 230 publications
(329 citation statements)
references
References 42 publications
17
286
2
13
Order By: Relevance
“…This observation is in accordance with a previous study showing that charged N-terminal residues were relatively protected from ERAP1 degradation (35). In vitro studies using synthetic peptides have shown that ERAP1 polymorphisms have substrate-dependent effects on enzyme activity (7,(36)(37)(38). A recent cell-based study showed that protective ERAP1 polymorphisms resulted in increased length and altered P1 residues of peptides bound to HLA-B*27:04 (39).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This observation is in accordance with a previous study showing that charged N-terminal residues were relatively protected from ERAP1 degradation (35). In vitro studies using synthetic peptides have shown that ERAP1 polymorphisms have substrate-dependent effects on enzyme activity (7,(36)(37)(38). A recent cell-based study showed that protective ERAP1 polymorphisms resulted in increased length and altered P1 residues of peptides bound to HLA-B*27:04 (39).…”
Section: Discussionsupporting
confidence: 92%
“…We and other investigators have shown that recombinant K528R ERAP1 has a slower substrate-trimming rate in vitro compared with WT ERAP1 (7,36,37). We therefore investigated whether cells transfected with K528R ERAP1 would present the KK10 peptide differently from those transfected with WT ERAP1.…”
mentioning
confidence: 97%
“…Four of the six (82, 102, 115, and 199) together with residue 127 are located in domain I away from the active site. Interestingly, the end of the S1 specificity pocket in domain II borders residues 181 and 183 in domain I and, therefore, the observed polymorphisms may affect the formation of the catalytic site (14,20). In addition, residue 127 may affect conformational transition from open to closed states as proposed (21).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, haplotypes K528/D575/R725, K528/D575/E730, R528/D575/R725/E730, and K528/D575/R725/Q730 have been shown to be associated with AS (10)(11)(12). The in vitro assessment of single amino acid ERAP1 variants corresponding to the AS-associated SNPs revealed reduced trimming activity for R528, Q725, and E730 but not N575 (2,13,14). Additional ERAP1 polymorphisms may contribute to function and/or disease association because fine mapping SNP analysis of ERAP1 identified the presence of additional SNPs in AS patients (3).…”
mentioning
confidence: 99%
“…8,9 In an effort to discover novel, nonpeptidic scaffolds that inhibit ERAP1 as leads for preclinical development we applied a combination of structure-based, ligand-based, and knowledge-based virtual screening approaches, taking advantage of key structural characteristics revealed in the recent crystal structures of ERAP1 and ERAP2 and their complexes with 1 and 2, respectively. 8,10,11 Toward this goal, we compiled a library of more than 265,000 compounds from selected collections of chemical vendors that are focused on drug-likeness and structural diversity (Table S1). The library was enriched with the National Cancer Institute's diversity set II (1364 compounds) and the DrugBank database comprising 6590 FDA-approved and experimental small-molecule drugs 12 We also performed a 3D pharmacophore search against the purchasable subset of the ZINC database (more than 20 million compounds) 13 using the online interface of ZINCPharmer.…”
Section: E Ndoplasmic Reticulum (Er) Aminopeptidases Generatementioning
confidence: 99%